Fairy tales from the Philippines - Robertson, Dorothy Lewis (New York Dodd & Mead, 1971)
Eleven fairy tales of the Philippines with such native touches as princesses that live in thatched huts, talking jellyfish, and tropical settings.
1
Keywords: Fairy tales -- Philippines